Willa of dark hollow - Beatty, Robert, 1963- (Disney-Hyperion, 2021)
"Willa and her clan are the last of the Faeran, an ancient race of forest people who have lived in the Great Smoky Mountains for as long as the trees have grown there. But as crews of newly arrived humans start cutting down great swaths of the forest she loves, she is helpless to stop them ... When Willa discovers a mysterious dark hollow filled with strange and beautiful creatures, she comes to realize that it contains a terrifying force that seems to be hunting humans ... Willa must find a way to save the people and animals she loves and take a stand against a consuming darkness that threatens to destroy her world"--